2008
DOI: 10.1007/s00383-008-2209-6
|View full text |Cite
|
Sign up to set email alerts
|

NKCC-1 and ENaC are down-regulated in nitrofen-induced hypoplastic lungs with congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) is accompanied by pulmonary hypoplasia and pulmonary hypertension. Fetal lung growth is dependent on the secretion of lung liquid, which normally is absorbed at partus. The ion channel NKCC-1 is involved in this secretory process, but has recently also been reported to be implicated in absorption. CDH patients show a disturbed transition from secretion to absorption. alpha- and beta-ENaC are essential for lung liquid absorption. Common for all transcellular ion transport i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…[29] In groups 3, 4 and 5 which received sildenafil and/ or bosentan, it was possible to attenuate pulmonary morphological, architectural and structural changes; especially those related to the abnormal development of the pulmonary vascular wall, as the characteristic of PPHN in patients with CDH and are the main cause of death of such patients. [30][31][32] Thus, group 3 which received sildenafi l, a specific phosphodiesterase 5 inhibitor, showed a dilated pulmonary vasculature and antiproliferative effects on cells of the pulmonary artery. [33] There was a significant reduction in arterial wall thickness in microns, which helped to mitigate the reduction of the vessel's lumen, expressed as the arterial-wall-lumen ratio.…”
Section: Discussionmentioning
confidence: 96%
“…[29] In groups 3, 4 and 5 which received sildenafil and/ or bosentan, it was possible to attenuate pulmonary morphological, architectural and structural changes; especially those related to the abnormal development of the pulmonary vascular wall, as the characteristic of PPHN in patients with CDH and are the main cause of death of such patients. [30][31][32] Thus, group 3 which received sildenafi l, a specific phosphodiesterase 5 inhibitor, showed a dilated pulmonary vasculature and antiproliferative effects on cells of the pulmonary artery. [33] There was a significant reduction in arterial wall thickness in microns, which helped to mitigate the reduction of the vessel's lumen, expressed as the arterial-wall-lumen ratio.…”
Section: Discussionmentioning
confidence: 96%
“…Expression of the ␣ 1 -subunit in rat and mouse lung increases from low levels throughout gestation and peaks just before or at birth [43,44] . No significant changes have been demonstrated in Na + , K + -ATPase ␣ 1 expression in nitrofen-induced CDH in rats, even though a tendency towards downregulation has been reported by our group before [24] . The decrease that we observe in CDH patients is pronounced.…”
Section: Discussionmentioning
confidence: 63%
“…This association was first showed in 2006 by Folkesson et al [22] , who reported a markedly impaired postnatal lung fluid transport and decreased protein levels of ENaC in nitrofen-induced CDH in rats. A recent study from our group has demonstrated low protein levels of ␤ -ENaC and Na + -K + -2Cl -cotransporter (NKCC-1) in hypoplastic CDH rat lungs [24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations